Helicobacter pylori Infection of Human and Murine Primary Gastric Cells - Clyne, Marguerite (American Society for Microbiology, 2004)
The effect of Helicobacter pylori infection on human and murine primary gastric cells was determined. CagA was phosphorylated following adherence of H. pylori to primary human gastric cells. However, it did not adhere to human primary duodenal cells or murine gastric cells, and CagA could not be detected in cell lysates. Identification of an easily available animal model of infection in which the organism adheres to gastric mucosal cells would enhance studies of the virulence of H. pylori.